On the Concept of an Organ of State - Pospieszalski, Karol Marian (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2019)
The paper is an English translation of O pojęciu organu państwowego by Karol Marian Pospieszalski, published originally in “Ruch Prawniczy Ekonomiczny i Socjologiczny” in 1972. The text is published as a part of a jubilee edition of the “Adam Mickiewicz University Law Review. 100th Anniversary of the Faculty of Law and Administration” devoted to the achievements of the late Professors of the Faculty of Law and Administration of the Adam Mickiewicz University, Poznań.